Sleep and Circadian Rhythms in Survivors of Acute Respiratory Failure - Yang, Pei-Lin; Ward, Teresa M.; Burr, Robert L.; Kapur, Vishesh K.; McCurry, Susan M.; Vitiello, Michael V.; Hough, Catherine L.; Parsons, Elizabeth C. (Frontiers in Neurology, 2020)
Background: Little is known about sleep and circadian rhythms in survivors of acute respiratory failure (ARF) after hospital discharge. Objectives: To examine sleep and rest-activity circadian rhythms in ARF survivors three months after hospital discharge, and to compare them with a community-dwelling population. Methods: Sleep diary, actigraphy data, and insomnia symptoms were collected in a pilot study of 14 ARF survivors. Rest-activity circadian rhythms were assessed with wrist actigraphy and sleep diary for nine days, and were analyzed by cosinor and nonparametric circadian rhythm analysis. Results: All participants had remarkable actigraphic sleep fragmentation, 71.5% had subclinical or clinical insomnia symptoms. Compared to community-dwelling adults, this cohort had less stable rest-activity circadian rhythms (p<0.001), and weaker circadian strength (p<0.001). Conclusion: Insomnia and circadian disruption were common in ARF survivors. Sleep improvement and circadian rhythm regularity may be a promising approach to improve quality of life and daytime function after ARF.